Communicative competence in technical oral presentation: Perspective of ESL educators and professional engineer - Bhattacharyya, E. (Universiti Putra Malaysia, 2014)
Communicative competence is one of the most highly sought after skills of prospective graduates among employers. In spite of its importance, the notion of communicative competence has been deemed fuzzy in Communication and Engineering studies. This fuzziness has undoubtedly led to tensions among stakeholders like educators and professional engineers across disciplinary tenures in interpreting the said notion. The study seeks to investigate the perceptions and understanding of educators and professional engineers of the notion in terms of two main elements of communicative competence: linguistic and rhetorical competence. The educators are language lecturers who conduct a speaking course for final-year Engineering-project students while the professional engineers are engineers from various Oil Producing Units (OPU) of the national oil company, PETRONAS, who have been selected as examiners to assess the said students' technical oral presentation. The professional engineers have been chosen by the university selection committee based on their years of working experience and professional expertise in engineering. Both language lecturers and the professional engineers were interviewed to gauge their perceptions on linguistic and rhetorical features deemed necessary to enhance communicative competence for the workplace. Both groups articulated awareness of the similarities and differences between the sub-sets of communicative competence, namely, technical, disciplinary, rhetorical style, interactive and interpersonal competence. Sublime differences in the way educators and professionals from different disciplines perceive communicative competence indicate possible reference to learning theory. Despite such disparity, pedagogical efforts are required to enhance communicative competence on such opportune platforms prior to the graduates' entry to the workplace. Â© Universiti Putra Malaysia Press.